전후 활주형 가동형 슬관절 전치환술 후 발생한 대퇴 치환물의 파손 - 정광환(Kwang-Hwan Jung); 나성천(Sung-Cheon Na); 최소연(So-Yeon Choi); 박기봉(Ki-Bong Park) (The journal of the Korean Orthopaedic Association, 2022)
저자들은 내원 7년 전 전후 활주형 가동형을 이용한 슬관절 전치환술을 받고 4주 전 극심한 좌측 슬관절 통증과 굴곡 제한이 발생한 78세 여자 환자에서 대퇴 치환물의 파손을 진단하고 재치환술을 시행하였다. 슬관절 전치환술 후 대퇴 치환물의 파손은 드문합병증으로 알려져 있으며, 다양한 인자들이 대퇴 치환물의 파손의 원인으로 이해되고 있기에 문헌 고찰과 함께 보고하는 바이다. The authors diagnosed femoral component fracture after total knee arthroplasty (TKA) using an anterior-posterior glide mobile-bearing system in a 78-year-old female patient who visited with severe pain and flexion limitations in the left knee and performed revision TKA. The fracture of the femoral component after TKA is a rare complication, and various factors cause the fracture of the femoral component. This case is reported along with a literature review. KCI Citation Count: 0